Killing in Style. - Dmitriev, Sviatoslav (Mnemosyne, 2016)
This article reconsiders divergent accounts of the events leading to the death of Demosthenes, and suggests to explain their coexistence by attributing them to either the historical tradition from Hellenistic times or the rhetorical tradition of the Roman period. The latter should be traced to progymnasmata, or fictional rhetorical compositions, which manipulated historical evidence and continued to surface in the writings of students of rhetoric. When put together, the stories of the death of Demosthenes offer a case study on how history writing and rhetorical education mutually influenced each other in the late Hellenistic and Roman periods.